Role of NF-kβ factor Rel2 during Plasmodium falciparum and bacterial infection in Anopheles dirus. Issue 1 (December 2016) - Khan, Mohammad; Liew, Jonathan; Leong, Cherng; Lau, Yee-Ling
Abstract Background Anopheles mosquitoes transmit malaria which is one of the world's most threatening diseases.Anopheles dirus (sensu stricto ) is among the main vectors of malaria in South East Asia. The mosquito innate immune response is the first line of defence against malaria parasites during its development. The immune deficiency (IMD) pathway, a conserved immune signaling pathway, influences anti-Plasmodium falciparum activity inAnopheles gambiae, An. stephensi andAn. albimanus . The aim of the study was to determine the role ofRel2, an IMD pathway-controlled NF-kappaβ transcription factor, inAn. dirus. Methods RACE (Rapid amplification of cDNA ends) was performed on theRel2 gene. Double-strandedRel2 was constructed and injected into the thorax of female mosquitoes. The injected mosquitoes were fed on aP. falciparum gametocyte culture and dissected on day 7–9 post-feeding in order to count the oocysts. A survival analysis was conducted by exposing the dsRNA injected mosquitoes to Gram-positive and Gram-negative bacteria. Results This study demonstrated that theRel2 gene inAn. dirus has two isoforms, short length and full length. RNA interference-mediated gene silencing ofRel2 showed that the latter is involved in protection againstP. falciparum, Gram-positive bacteria (Micrococcus luteus ) with Lys-type peptidoglycan and Gram-negative bacteria (Escherichia coli ) with DAP-type peptidoglycan. Conclusion This study suggested that there are similarities in the splicing events and functionality of theRel2 gene, between theAnopheles species. Among all the important anophelines, the immunity of only a few has been thoroughly investigated. In order to develop novel vector-based control strategies and restrict malaria transmission, the immune pathways of these important vectors should be thoroughly investigated.